Validation of WHOQOL-BREF in Malayalam and Determinants of Quality of Life Among People With Type 2 Diabetes in Kerala, India - Aswathy Sreedevi;Sandhya Cherkil; Deepak Soman Kuttikattu; Leelamoni Kamalamma and Brian Oldenburg
Quality of life (QOL) is an important health outcome in people with chronic conditions like diabetes and WHOQOL-BREF is a popular instrument used worldwide to assess QOL. However, QOL varies considerably from society to society depending on the culture of the person. Hence, the WHOQOL-BREF was translated to the local language, Malayalam. This article attempts to establish reliability, construct and discriminant validity of the translated WHOQOL-BREF, and determinants of QOL among people with type 2 diabetes. A cross- sectional study was undertaken among 200 patients with diabetes attending a primary care center in a rural area of Kerala, India. The translated version of WHOQOL-BREF was found to be internally consistent (Cronbach’s α = .86) and demonstrated discriminant and construct validity. Education was found to be an independent determinant of QOL in the physical, psychological, and environmental domains. Thus, the translated version had good psychometric properties and education was an independent determinant of QOL in 3 of 4 domains.